Evaluating the Deterrence Effect of Criminal Proceedings and Sanctions - Hamzaoğlu, Nurcan; Türk, Burcu; Sanal, Yasemin (The Bulletin of Legal Medicine, 2019)
The present study aimed to evaluate the perceptions and attitudes of the participants regarding the deterrence of penalties, investigation and prosecution processes.The study was carried out with a total of 912 people with an age range of 18-64 years (mean age 33,0 ± 9,3) via online application of the survey created by the researchers.As a result, the type of crime, which is considered by the participants as having the most probability of being seized, is the commitment of murder (63,8%). The ratio of the participants who stated that the inefficiency in making an investigation is influential in not detecting crime is 69%.  While 25,1% of the participants think that criminal punishments are efficient for deterrence; 67,4% of the participants believe that abatement due to effective repentance decreases the effectiveness of deterrence. 70,8% of the participants, on the other hands, think that good conduct time decreases the effectiveness of deterrence in committing a crime. While 13,4% of the participants say that "they would commit a crime if they knew they wouldn't get caught", 55,9% of the participants who believe that the possibility of being seized because of committing a crime is high.In accordance with the data obtained from the study; it is thought that the perceptions about the offender “cannot escape the punishment to be given in any way”, “will be punished in a short time” and “the penalties are commensurate with the crime” should ve improved in order to reduce the crime rate or to prevent the crimes.
Keywords: Crime and Punishment; Deterrence; attitude; perception; forensic sciences